Estudio de viabilidad ambiental y financiero sobre las técnicas de la construcción sostenible que pueden adoptarse en la construcción tradicional de viviendas en Colombia (2020)
The overpopulation and expansion of cities through the construction of houses has generated effects on the environment that have contributed to the climate crisis that the planet is currently experiencing, the indiscriminate use of natural resources, land occupation and the generation of waste have produced impacts that could be counteracted through the concept of sustainability, which mitigates and controls the effects generated during the construction processes contributing to the improvement of the environment, which is why an environmental and financial feasibility study is proposed on sustainable construction techniques that can be adopted in the traditional construction of houses in Colombia, seeking through the incorporation of sustainable materials such as Hempcrete, hydraulic concrete made of hemp fibers and sustainable techniques such as Evapotranspiration, rainwater collection roofs, solar panels and treatment plants of waters optimizing environmental conditions while providing quality of life and calculating the environmental impacts on water, air and soil to have a perspective on the environmental and financial viability of adapting sustainable techniques to the traditional construction system without pretending At no time should the home be sustainable, since to be considered sustainable, requirements must be met that are not the focus of this work.